EVALUATION OF THE INTERFERENCE IMPACT ON THE TRANSMISSION RATE OF VDSL2 SYSTEMS OPERATING OVER TPP AND UTP CAT 5E CABLES - Орєшков, Василь; Макаров, Ігор; Стеля, Дмитро; Скрипник, Юлія (SWorldJournal, 2025)
The paper presents an evaluation of the impact of interference noise on the transmission rate of VDSL2-based transmission systems. The study considers the operation of VDSL2 transmission systems over TPP 10×2×0,4 and UTP Cat5e 4×2×0,5 cables using both cl